ABOUT FEATURES OF LAND VALUATION: Array - Kobzan, S. (Municipal economy of cities (Technical science), 2019)
The purpose of the article is to investigate the market of land plots. The author poses the problem of determining the land in different laws and not implementing in practice these documents.Particular attention is paid to the research of the market of land for commercial purposes. The article analyzes the market of land plots. Investigated offers within the city and calculated the average cost of land for commercial purposes. Considerable attention is paid to the peculiarities of land valuation of commercial purposes. The author systematized factors that affect the value of land: Economic factors that depend on the macroeconomic situation and the economic situation in the region. Political factors. Factors are related to the political situation in the country. Market factors. Market factors include demand and supply and its market elasticity and other factors inherent in a normally functioning real estate market as an element of a market economy. Socio-demographic factors. Factors due to state regulation of the land market. Factors reflecting the physical characteristics of the site and the environmental impact - it is necessary to take into account the influence of these factors. External factors The author identified the stages of calculating the market value of land for commercial purposes. The author pays special attention to the most effective use of the earth. The author made a conclusion on the direct - proportional dependence of market value of land from infrastructure in the course of own research.